The Relationship Between Organizational Culture, Human Resource Management Practices And Organizational Performance: The Case Of Jordanian Insurance Sector - Anas Mahmoud Khaled Bashayreh
Insurance is one of the cornerstones of the modern-day financial services sector. In addition to its traditional role of managing risk, the insurance sector promotes long term savings and serves as a conduit to channel funds from policyholders to investment opportunities, including mortgage lending. As such, a thriving insurance sector is not only evidence of an efficient financial services sector, but it is also a key enabler of a healthy economy. The present study aims to determine the understanding for conceptual of organizational culture, and study the relationship between the organizational culture, human resource management practices, and organizational performance. As well, to determine the mediating effect of human resource management practices on the relationship between organizational culture and organizational performance. This study attempted as a first empirical study in the Jordanian insurance sector. Nine dimensions of organizational culture namely supportiveness, emphasis on rewards, behavioral styles, innovation, performance oriented, stability and communication, encourage development, policies and procedures, and organizational expectation, along with five dimensions of human resource management practices requirement and selection, career planning, compensation, training & development, job description, and organization performance factors. To achieve research objectives the researcher used a quantitative method. A survey was carried out among 327 employees, who were selected using a cluster sampling technique from 28 insurance companies. The instrument measures the personality construct, organizational culture dimensions, human resource management practices, and organizational performance. Factor analysis, multiple regression analysis, and structural equation model were employed to examine their dimensionality, ensure internal consistency and validity, as well as to test the hypothesis. The finding shows that there are correlation between organizational culture and human resource management practices (r = 0.810), and between organizational culture and organizational performance (r = 0.649), as well between human resource management practices and organizational performance (r = 0.687). In addition, the present study revealed the mediating effect of human resource management practices on the relationship between organizational culture and organizational performance (r= 0.908). In particular, the study found that innovation from organizational culture dimensions, most contribute to organizational performance (β= 0.260). The implications and suggestions of the present study on future research and practice are discussed.